If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1a = -1(d + -4) Reorder the terms: 4 + -1a = -1(-4 + d) 4 + -1a = (-4 * -1 + d * -1) 4 + -1a = (4 + -1d) Add '-4' to each side of the equation. 4 + -4 + -1a = 4 + -4 + -1d Combine like terms: 4 + -4 = 0 0 + -1a = 4 + -4 + -1d -1a = 4 + -4 + -1d Combine like terms: 4 + -4 = 0 -1a = 0 + -1d -1a = -1d Solving -1a = -1d Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '-1'. a = d Simplifying a = d
| 1=8-3x | | 5x+7=x+51 | | x^2+y^2-8x-4y+16=0 | | -3=0.27(-1)+b | | 8x-90=9x | | 8(y-4)=6y-18 | | 6k+8=12 | | 2x+8/3-7=4x+1 | | 11=6.4x-0.5(9.8)x^2 | | 5-3m=-2-2m | | 22=2l+2w+7 | | -128-11x=148+12x | | 2x+2=57-3x | | 3-2Y=9-8Y | | 12y^2+11y-15=0 | | 5x+7x-64=80-4x | | -11=6.4x+0.5(9.8)x^2 | | (5x-7)(13x-11)=0 | | -9x^2-18x-12=0 | | 7g-6=-6b+20 | | 2(2x)+2(x)=120 | | (9b-3)3= | | 2(x-2)+8=6(2x-4) | | .5(2y+4)-9=-.5(6y-10) | | 24(z-1)=4(5z+4) | | 2x+10-2x=6x-14 | | 4x+2=2x+5 | | 12=-10+2x | | -2x-4=7x-13 | | 2(p-6)-8(5p+2)=-38 | | -(-6r+8)=-7(r+3) | | 3(x-5)+6=3x-4 |